Acute tear of the fascia cruris at the attachment to the Achilles tendon: a new diagnosis. Issue 21 (8th September 2014) - Webborn, Nick; Morrissey, Dylan; Sarvananthan, Kasthuri; Chan, Otto
Abstract : Background: The fascia cruris encloses the posterior structures of the calf and connects to the paratenon and the Achilles tendon. We describe the clinical presentation, ultrasound imaging characteristics and the time to the recovery of tears of the fascia cruris at the attachment to the Achilles tendon. Methods: Retrospective review of 11 tears of the fascia cruris in the different legs as separate events in 9 patients (6 male and 3 female, mean age 35.52 years, range 11–48) identified using diagnostic ultrasound, after presenting with Achillodynia. Results: 11 participants presented at a mean of 4.5 weeks (range 0.5–12) after onset of symptoms. The left Achilles was more commonly injured than the right (7 : 4) and the lateral side more than the medial (6 : 4) with one case with medial and lateral presentation. Clinically, there was swelling and tenderness over the medial or lateral border in the mid to upper portion of the Achilles. 7 of the 11 (63.6%) had functional overpronation. Ultrasound appearances of a tear were identified as hypoechoic area extending from the medial or lateral border of the Achilles extending along the anatomical plane of the fascia cruris. Average return to activity was 5.2 weeks (range 1–22). Participants presenting later had longer recovery but all participants returned to full activity (r=0.4). Conclusions: This is the first description of the clinical details and sonographic findings of a tear to the fascia cruris at its attachment to the Achilles tendon. This needs to be considered as a cause of Achillodynia in athletes as recognition will affect the management.